2020
DOI: 10.1093/carcin/bgaa062
|View full text |Cite
|
Sign up to set email alerts
|

Oral microbial dysbiosis and its performance in predicting oral cancer

Abstract: Abstract Dysbiosis of oral microbiome may dictate the progression of oral squamous cell carcinoma (OSCC). Yet, the composition of oral microbiome fluctuates by saliva and distinct sites of oral cavity and is affected by risky behaviors (smoking, drinking, and betel quid chewing) and individuals’ oral health condition. To characterize the disturbances in the oral microbial population mainly due to oral tumorigenicity, we profiled the bacteria within the surface of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
105
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(113 citation statements)
references
References 45 publications
8
105
0
Order By: Relevance
“…In addition, in line with the previous studies ( 29 , 52 , 53 ) Firmicutes was also found as the most abundant phylum in overall oral microbiome in our study. Of the significantly elevated genera in cancerous lesions, Prevotella and Pseudomonus were previously shown to be highly abundant in both periodontitis and OSCC samples when compared to healthy controls ( 32 , 53 , 59 ). Importantly, periodontitis has been suggested as a self-governing risk factor for OSCC development ( 27 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, in line with the previous studies ( 29 , 52 , 53 ) Firmicutes was also found as the most abundant phylum in overall oral microbiome in our study. Of the significantly elevated genera in cancerous lesions, Prevotella and Pseudomonus were previously shown to be highly abundant in both periodontitis and OSCC samples when compared to healthy controls ( 32 , 53 , 59 ). Importantly, periodontitis has been suggested as a self-governing risk factor for OSCC development ( 27 ).…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with Guerrero-Preston et al study ( 51 ), we also observed a significant loss in richness and diversity of oral bacterial communities in OSCC lesions compared to matched controls. However, several reports revealed enhanced diversity of bacterial communities in OSCC samples ( 31 , 52 , 53 ). Nevertheless, dysbiosis of oral microbiome appears to be strongly associated with OSCC development.…”
Section: Discussionmentioning
confidence: 99%
“…119,120 Recently, a study suggests that compared with the controls, microbial pathway modules associated with the metabolism of terpenoids and polyketides, including the biosynthesis of siderophore group nonribosomal peptides, monoterpenoid biosynthesis, and biosynthesis of 12-, 14-and 16-membered macrolides, are less abundant in oral tumor lesions. 28 In conclusion, these findings reveal that the oral microbiota community dynamically changes and potentially induces oral lesion progression. These findings highlight a novel aspect of OLK and OSCC etiology and the functional role of the oral microbiome in formulating a tumor microenvironment via the attenuated biosynthesis of secondary metabolites with cancer-promoting or anti-cancer effects.…”
Section: Microbial Signals In Oral Leukoplakia and Oral Squamous Cell Carcinomamentioning
confidence: 70%
“…[20][21][22][23][24] An increasing body of evidence suggests that perturbations of the mucosal microbiota can modulate innate and adaptive immune responses, with inflammation arising due to a reduction in the number of symbiont microorganisms and/or an increase in the number of pathobiont microorganisms (commensal bacteria with pathogenic potential). [25][26][27][28] For example, one mechanism by which these microbes regulate immunity is by controlling regulatory T cells (Tregs) and T helper 17 (Th17) cells. [29][30][31] In addition, the epithelium recognizes and responds to the microbiota, and in turn, microbial dysbiosis and associated metabolite alterations destroy the integrity of the mucosal epithelium and its barrier functions.…”
mentioning
confidence: 99%
“…cancer, the search for possible biomarkers of oral cancer and, most specifically, OSCC has not produced conclusive results(52). Different organisms have been shown to increase in OSCC samples, as a few examples: Capnocytophaga gingivalis, Prevotella melaninogenica, and S. mitis (131); F. nucleatum(149); Pseudomonas aeruginosa (150); Campylobacter concisus, Prevotella salivae, Prevotella loeschii, and Fusobacterium oral taxon 204(151); genera Fusobacterium, Dialister, Peptostreptococcus, Filifactor, Peptococcus, Catonella, and Parvimonas (136); and Prevotella oris, Neisseria flava, Neisseria flavescens/subflava, F. nucleatum ss polymorphum, Aggregatibacter segnis, and Fusobacterium periodonticum(152).…”
mentioning
confidence: 99%